High MBL-expressing genotypes are associated with deterioration in renal function in type 2 diabetes - Dørflinger, G. H.; Høyem, P. H.; Laugesen, E.; Østergaard, J. A.; Funck, K. L.; Steffensen, R.; Poulsen, P. L.; Hansen, T. K.; Bjerre, M. (Frontiers in Immunology, 2022)
Introduction Accumulating evidence support that mannan-binding lectin (MBL) is a promising prognostic biomarker for risk-stratification of diabetic micro- and macrovascular complications. Serum MBL levels are predominately genetically determined and depend on MBL genotype. However, Type 1 diabetes (T1D) is associated with higher MBL serum levels for a given MBL genotype, but it remains unknown if this is also the case for patients with T2D. In this study, we evaluated the impact of MBL genotypes on renal function trajectories serum MBL levels and compared MBL genotypes in newly diagnosed patients with T2D with age- and sex-matched healthy individuals. Furthermore, we evaluated differences in parameters of insulin resistance within MBL genotypes. Methods In a cross-sectional study, we included 100 patients who were recently diagnosed with T2D and 100 age- and sex-matched individuals. We measured serum MBL levels, MBL genotype, standard biochemistry, and DEXA, in all participants. A 5-year clinical follow-up study was conducted, followed by 12-year data on follow-up biochemistry and clinical status for the progression to micro- or macroalbuminuria for the patients with T2D. Results We found similar serum MBL levels and distribution of MBL genotypes between T2D patients and healthy individuals. The serum MBL level for a given MBL genotype did not differ between the groups neither at study entry nor at 5-year follow-up. We found that plasma creatinine increased more rapidly in patients with T2D with the high MBL expression genotype than with the medium/low MBL expression genotype over the 12-year follow-up period (p = 0.029). Serum MBL levels did not correlate with diabetes duration nor with HbA1c. Interestingly, serum MBL was inversely correlated with body fat percentage in individuals with high MBL expression genotypes both at study entry (p=0.0005) and 5-years follow-up (p=0.002). Discussion Contrary to T1D, T2D is not per se associated with increased MBL serum level for a given MBL genotype or with diabetes duration. Serum MBL was inversely correlated with body fat percentage, and T2D patients with the high MBL expression genotype presented with deterioration of renal function.